Freeze-Dried Phycocyanin Microcapsules: Effect of Maltodextrin-Soy Protein Ratios on Encapsulation Efficiency and Particle Properties - Siti Aisiyah; Ira Juliani Anwar; Dian Marlina; Ana Indrayati; Desi Purwaningsih (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Natural pigments such as phycocyanin are highly sensitive to environmental conditions and therefore require stabilization to broaden their applications in functional products. This study aimed to evaluate the effect of varying ratios of maltodextrin and soy protein isolate (SPI) on the physical properties and encapsulation performance of freeze-dried phycocyanin microcapsules. Phycocyanin was extracted using phosphate buffer and encapsulated in three formulations with different maltodextrin–SPI proportions. The obtained microcapsules were characterized using UV–Vis spectrophotometry and particle size analysis (PSA) to determine encapsulation efficiency (EE), yield, moisture content, purity index, and particle size distribution. All experiments were performed in triplicate (n = 3), and data were analyzed using one-way ANOVA (p < 0.05). The formulation with a higher proportion of maltodextrin exhibited the best performance, achieving high EE (≈96%), low moisture content, and uniform particle size. These findings highlight that optimizing biopolymer combinations can enhance the quality and stability of phycocyanin microcapsules, demonstrating potential applications in functional food and pharmaceutical formulations.